Modelos de crescimento de cultivares de centeio - Kleinpaul, Jéssica Andiara (2018)
The objectives of this study were to adjust the nonlinear models, Gompertz and Logistic, to describe the plant height, fresh matter of aerial and dry matter of aerial and indicate the model that best describes the growth of two rye cultivars, BRS Progresso and Temprano, in five sowing seasons. Ten uniformity trials were conducted with the rye crop in the 2016 harvest. Ten plants weekly were evaluated from the first leaf to be fully expanded, randomly chosen within each assay. In each plant were evaluated the characters of plant height, fresh matter of aerial and dry matter of aerial. For the adjustment of the Gompertz and Logistic models as a function of the accumulated thermal sum, the mean value of each character in each evaluation was considered. Were estimated parameters a, b and c for each model. The confidence interval for each parameter, inflection points, maximum acceleration, maximum deceleration and asymptotic deceleration was calculated. The quality of fit of the models was verified by the coefficient of determination, Akaike's information criterion and residual standard deviation. For analysis of the behavior of the models, the nonlinearity present in the models was quantified through the intrinsic nonlinearity and the nonlinearity of the parameter effect. Both models satisfactorily describe the behavior of the characters in rye cultivars at sowing times. The model that best describes the growth behavior of rye cultivars is the Logistic model.